Organized Crime Like Modern Security Problem: Characteristics and Development (Kriminalističke teme, 2003)
Organized crime in modem therms takes on new forms contents, gains international dimention and has negative consequences on national and international security.Caracterized by changes in organizational structure of organized criminal groups and organizations phenomenon of new form of crime by return of patem which were thought to be long past, roothed out or long forgotten; increased degree of society peril of new pattern of criminal form in regard of specificity of victims and the way is carried out; conections of politicians from former regime and their aspirations to actively be involved in new regime. It alowed the organized criminal, in certain cases, to be the step ahead to security sistem.Compatibility and interwining with the other forms of jeopardizing safety (internal and external, unarmed and armed) and activity of international plan, gives the new caracter and meaning to organized crime. Traditionaly understood as internal non armed form of jeopardizing safety, organized criminal element has taken external form of jeopardizing safey of state and society, for which suppresion the international colaboration